Spin-liquid-like state in a spin-1/2 square-lattice antiferromagnet perovskite induced by d 10–d 0 cation mixing - O. Mustonen (Nature Portfolio, 2018)
Quantum spin liquids are predicted to form in frustrated square lattice magnets but this has been difficult to verify experimentally. Here the authors show that cation mixing in the square perovskite Sr2Cu(Te0.5W0.5)O6 can be used to tune it into the spin liquid regime.